Sosialisasi Storytelling Melalui Media Gambar Pada Anak Usia Dini - Nissa, Khairun; Putri, Jihan Hidayah (Sekolah Tinggi Ilmu Manajemen Sukma Medan, 2025)
Literacy and speaking skills in early childhood are the primary foundations for their cognitive and socio-emotional development. However, challenges in the field indicate a persistent need for more interactive and enjoyable learning methods to stimulate these abilities. This community service program aims to socialize the storytelling method using picture media for children at the Fadilah Rahma Foundation, covering the Pekan Labuhan and Panah Hijau areas. The implementation methods used in this activity include lecture techniques through creative fairytale narration titled